Selection of appropriate scale of relief model - Kuźma, Marta; Lisowski, Marcin (International Conference “Environmental Engineering”, 2017)
This paper presents the application of digital terrain model in developing a relief model. The digital terrain model served as the basis for the relief model. The research has taken into account the subject of combining different data in order to develop a numerical model of the land − surveying, bathymetry, maps. Another issue addressed was the one of vertical scale or exceeding it in the developed model. Its appropriate selection allows the correct representation of the terrain geomorphology. The paper presents research in carrying out relief model of Szczęśliwicki Park in Warsaw. The results show the link between the vertical scale or exceeding it and the accuracy (correctness) of relief model in large-scale descriptions. In addition, a verification of models was made with the use of a scanner that uses structural light.